To solve the equation \(3x + 5y = 60\) for \(y\), we need to isolate \(y\).
Starting with the equation:
\[ 3x + 5y = 60 \]
we can subtract \(3x\) from both sides:
\[ 5y = 60 - 3x \]
Next, we divide both sides by \(5\):
\[ y = \frac{60 - 3x}{5} \]
This simplifies to:
\[ y = 12 - \frac{3}{5}x \]
Now, let's analyze the given responses to find the correct one:
- \(y = 60 + \frac{3x}{5}\) - Incorrect.
- \(y = 60 - 3x\) - Incorrect.
- \(y = -\frac{3}{5}x + 12\) - Correct (it matches the simplified version).
- \(y = 57x/5\) - Incorrect.
The correct answer is:
y = -\frac{3}{5}x + 12